OFR-5-74 Summary Of Heavy Metals Study At San Juan Ridge, Nevada County, California - Russell R. McLellan (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The Tertiary channel gravel deposits in northern California were selected Or detailed investigation by the U. S. Bureau of Mines as part of a national program to locate potential sources of gold that might be developed rapidly by large-scale mining operations. Five bureau research centers representing mining and metallurgy subsystems coordinated their efforts in a team operation to identify and investigate possible solutions to the problem area, that long have discouraged the resumption of large-scale mining in the deposits. This report summarizes the individual investigations, conclusions and recommendations conducted and prepared by all mining subsystems research groups after the completion of two years of field work at the deposits on San Juan Ridge in Nevada County, California. The studies indicate that modern mining technology can cope with the environmental problems that closed the immense hydraulic mines in 1,884. however, they also indicate that mining can be conducted with only marginal profits its unless the price of gold remains substantially above $70 per ounce or unless sufficient by-products can be recovered and sold to place the average value per cubic yard of gravel into a positive commercial range. The by-product potential of the Tertiary gravels remains to be investigated in more detail.